Keadilan Pemilu Dalam Perkara Pidana Pemilu: Studi terhadap Putusan Pengadilan - Suparto; Despan Heryansyah (Fakultas Hukum Universitas Islam Indonesia, 2022)
Electoral justice can be seen from at least two important aspects, namely the procedure of the election implementation and the mechanism for resolving election-related offences. Election-related offences are understood as actions that are contrary to the provisions of laws and regulations relating to elections. One of the said election-related offences is resolved through the District Court. However, reflecting on the completion of criminal acts in the 2019 legislative elections, electoral justice has not been successful. Of all the decisions of the District Courts in Yogyakarta and West Sumatra that have been analyzed, all of them issued probation to the perpetrator, regardless of the position of the perpetrator, the type of crime, and other aggravating reasons at trial. This study looks at the tendency of judges in deciding cases of election criminal violations and encourages the optimization of electoral justice in these decisions. This normative legal research emphasizes the use of secondary data, especially the decisions of District Court judges in Yogyakarta and West Sumatra. The results of the study show that first, the tendency of decisions to give very light sentences to perpetrators. Second, electoral justice has not been optimally obtained through the District Court because of the lightness of the sentence issued. This is because judges only consider the juridical aspect alone, without seeing the election as a real implementation of the sovereignty of the people as well as various other philosophical and sociological considerations. Key Worsd: Electoral justice; election crime; judge decision Abstrak Keadilan pemilu setidaknya dapat dilihat dari dua aspek penting, yaitu terkait prosedur pelaksanaan Pemilu dan mekanisme penyelesaian pelanggaran Pemilu. Pelanggaran Pemilu dipahami sebagai tindakan yang bertentangan dengan ketentuan peraturan perundang-undangan terkait Pemilu. Salah satu pelanggaran Pemilu dimaksud diselesaikan melalui Pengadilan Negeri. Namun, bercermin pada penyelesaian tindak pidana pemilu legislatif 2019 lalu, keadilan pemilu belum berhasil diwujudkan. Dari keseluruhan putusan Pengadilan Negeri di DIY dan Sumatera Barat yang dianalisis, seluruhnya memberikan pidana percobaan kepada pelaku, tanpa memperhatikan kedudukan pelaku, jenis tindak pidana, dan alasan pemberat lainnya di persidangan. Penelitian ini melihat kecenderungan hakim dalam memutus perkara pelanggaran pidana pemilu dan mendorong optimalisasi keadilan pemilu dalam putusan tersebut. Penelitian hukum normatif ini menekankan pada penggunaan data sekunder, terutama putusan hakim Pengadilan Negeri di DIY dan Sumatera Barat. Hasil penelitian menyimpulkan bahwa pertama, kecenderungan putusan memberikan hukuman yang sangat ringan terhadap pelaku. Kedua, keadilan pemilu belum optimal didapatkan melalui Pengadilan Negeri karena ringannya hukuman yang dijatuhkan. Ini disebabkan hakim hanya mempertimbangkan aspek yuridis semata, tanpa melihat pemilu sebagai implementasi nyata dari kedaulatan rakyat serta berbagai pertimbangan folosofis dan sosiologis lainnya. Kata Kunci: Keadillan pemilu; tindak pidana pemilu; putusan hakim